Design and creation of an employee performance appraisal information system using the web-based management by objectives (MBO) method at PT. Tetra Grosir Indonesia - Farkhan, Mohamad; Sharyanto, Sharyanto; Ulan Bani, Alexius (Yayasan Bina Internusa Mabarindo, 2024)
PT Tetra Grosir Indonesia is a multipurpose store with various product categories. Currently, employee performance appraisal at PT Tetra Grosir Indonesia is still manual, causing problems such as fraud and errors in employee assessment. This process involves sending forms via WhatsApp, leading to delays and loss of information. In addition, the processing of the final report assessment results is still in paper form, which has the potential to be damaged or even lost. Therefore, to deal with these problems, a web-based employee performance appraisal application was created, in order to overcome problems of efficiency, accuracy, and reliability in the employee appraisal process. This application is designed and built using PHP as a programming language and MySQL as a database. With this application, it is expected to facilitate the employee appraisal process.